PENGARUH ORIENTASI ETIKA RELATIVISME, INTENSITAS MORAL, KOMITMEN ORGANISASI, SIFAT MACHIAVELLIAN DAN TINGKAT KESERIUSAN KECURANGAN TERHADAP INTENSI UNTUK MELAKUKAN WHISTLEBLOWING INTERNAL (Studi Empiris Pada OPD Kabupaten Rokan Hilir) - Arisna Rahmadani; Hardi Hardi; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This reseacrh was conducted on employees OPD Rokan Hilir. This reseacrh is the quantitative research. The type of data used in this reseacrh is the primary data. And then, in data collections sampling was conducted with a purposive sampling method with 108 employees who working in OPD Rokan Hilir as respondents. Analyzed using multiple regression with SPSS version 20. This reseacrh aimed to know the influence of the Relativism Ethical Orientation, Moral Intensity, Organizational Commitment, Machiavellian and seriousness of wrongdoing.to the Intention to carry out an Internal Whistleblowing. The main Problem that researcher descriptions are as follows: to see how many significant effect between the independent variable to the dependent variable. The result of the research showed that the Relativism Etchical Orientation have influence to the intention to carry out an Internal Whistleblowing, moral intensity have influence to the intention to carry out an Internal Whistleblowing, Organizational Commitment have influence to the intention to carry out an Internal Whistleblowing, Machiavellian have influence to the intention to carry out an Internal Whistleblowing and seriousness of wrongdoing.have influence to the intention to carry out an Internal Whistleblowing. So that all hypotheses presented in this research received.Keywords : Internal Whistleblowing, Relativism Etchical Orientation, Moral Intensity, Organizational Commitment, Machiavellian and seriousness of wrongdoing.